تحديد الاحتياج المائي لصنفي الحمضيات الحامض انترودوناتو والبرتقال أبو سرة باستخدام نظم ري مختلفة - غانم محمد; صافي زهر (Latakia University Journal -Biological Sciences Series, 2019)
يستهدف البحث تحديد الاحتياج المائي لصنفين من الحمضيات هما: الحامض انترودوناتو والبرتقال أبو سرة باستخدام نظم الري بالتنقيط، الري بالميكروجيت، الري الفقاعي والري السطحي، وقد بينت الدراسة ما يلي: لا تحتاج بساتين الحمضيات إلى ري خلال أشهر الشتاء (كانون الأول، كانون الثاني وشباط)، حيث كمية الأمطار الفعّالة أكثر من الاحتياج المائي للأشجار. إنّ الاحتياجات المائية لصنف الحامض انترودوناتو أعلى من الاحتياجات المائية لصنف البرتقال أبو سرة، حيث زاد معامل المحصول للحامض انترودوناتو بمقدار 5% عن معامل المحصول للبرتقال أبوسرة. بلغت كفاءات الري 0.938، 0.842، 0.815 و0.65 للري بالتنقيط، للري بالميكروجيت، للري الفقاعي وللري السطحي على التوالي. مع اعتبار الري السطحي كشاهد فقد بينت النتائج أنّه يمكن توفير كمية من المياه خلال سنة واحدة في كل هكتار بلغت لصنف الحامض انترودوناتو 3800 م3، 2820 م3 و2490 م3 ولصنف البرتقال أبو سرة 3440 م3، 2560 و2250 م3 باستخدام الري بالتنقيط، الري بالميكروجيت والري الفقاعي على التوالي. The research aimed to determine water requirements by using drip irrigation, microjet irrigation, bubbler irrigation and surface irrigation for citrus sorts: lemon antrodonato and navel orange. The study showed the following: The citrus fields did not need to be irrigated through the winter months (December, January, February) because of the effective rainfall which is more than what the trees require. the water requirements of lemon antrodonato were higher for lemon antrodonato than for navel orange, while the crop coefficient of lemon antrodonato was 5% higher than that of navel orange. The irrigation efficiencies were 0.938, 0.842, 0.815 and 0.65 for drip, microjet, bubbler and surface irrigation, respectively. By regarding the surface irrigation as a witness, we can economize water in one year for one hectare 3800 m3, 2820 m3 and 2490 m3 for lemon antrodonato and 3440m3, 2560m3 and 2250m3 for navel orange by using drip, microjet and bubbler irrigation, respectively.